Catalyst-free synthesis of quinazoline derivatives using low melting sugar–urea–salt mixture as a solvent - Zhang, Zhan-Hui; Zhang, Xiao-Nan; Mo, Li-Ping; Li, Yong-Xiao; Ma, Fei-Ping (Green chemistry : an international journal and green chemistry resource : GC, 2012)
Low melting mixture of maltose-dimethylurea (DMU)-NH4Cl was found to be an inexpensive, non-toxic, easily biodegradable and effective reaction medium in the catalyst-free synthesis of quinazoline derivatives. This simple and efficient method furnished the corresponding quinazolines in high yields via one-pot three-component reaction of 2-aminoaryl ketones, aldehyde, and ammonium acetate under aerobic oxidation conditions.